Seasonal changes in total body water; body composition and water turnover in reindeer - Larsen, Terje S.; Blix, Arnoldus Schytte (Rangifer, 1985)
Total body water and water turnover were measured at different times throughout the year in 3 captive Norwegian reindeer, using a tritiated water dilution method (Holleman et al. 1982). Total body water (percent of body weight) increased during late autumn and winter, from 59.1 ± 1.5 % in October to 72.5 ± 2.0 % in April. Using the equatation by Pace and Rathbun (1945) for predicting total body fat (% fat = 100 - % water/0.732), this increase in total body water indicates a concomitant reduction in body fat, from a maximum value of 18.9 ± 2.6 % (of body weight) in October to a minimum of 0.9 ± 2.7 % in April. During summer, on the other hand, fat content increased at the expense of a reduced percentage of body water. Water turnover was low in winter (December - April), ranging between 30.8 ± 5.2and43.6 ± 13.5ml.d-'. kg-1, but increased nearly fourfold during summer (June-August) with a maximum of 117.7 ± 5.9 ml.d-1. kg-1 in August. Positive correlations between water turnover and food intake and between water turnover and ambient temperature were found, the latter probably resulting from an incidental correlation between food intake and ambient temperature. Sesongmessige forandringer i totalt kroppsvann, kropps-sammensetning og vannomsetning hos reinsdyr. Abstract in Norwegian / Sammendrag: Totalt kroppsvann og vannomsetning av vann ble målt til forskjellige årstider i 3 norske reinsdyr ved hjelp av utvasking av tritiert vann (Holleman et al. 1982). Totalt kroppsvann (prosent av kroppsvekt) økte utover høsten og vinteren, fra 59.1 ± 1.5 % i oktober til 72.5 ± 2.0 % i april. Ved hjelp av en ligning som er gitt av Pace og Rathbun (1945) for beregning av totalt kroppsfett (% fett = 100 - % vann/0.732), fant en at denne økningen i vanninnhold tilsvarte en samtidig reduksjon i fettinnhold, fra en maksimums-verdi på 18.9 ± 2.6 % av kroppsvekt i oktober til et minimum på 0.9 ± 2.7 % i april. Utover sommeren økte derimot innholdet av fett på bekostning av vanninnholdet. Omsetningen av vann var lav vinterstid (desember - april), varierende mellom 30.8 ± 5.2 og 43.6 ± 13.5 ml.d-1.kg-1, men økte nesten fire ganger i løpet av sommeren (juni - august) til et maksimum på 117.7 ± 5.9 ml.d-1.kg-1 i august. Det ble funnet positive korrelasjoner mellom vannomsetning og forinntak og mellom vannomsetning og omgivelsestemperatur. Sistnevnte korrelasjon kan muligens skyldes en tilfeldig sammenheng mellom forinntak og omgivelsestemperatur. Vuodenaikaiset muutokset poron ruumiin kokonaisvesimååråsså, ruumiin koostumuksessa ja vesiaineenvaihdunnassa. Abstract in Finnish / Yhteenveto: Ruumiin kokonaisvesimaåråå ja vesiaineenvaihduntaa mitattiin eri vuodenaikoina 3 norjalaisella porolla kåyttåmållå apuna tritioitua vetta (Holleman et al. 1982). Ruumiin kokonaisvesimåarå (prosenttia ruumiinpainosta) lisåantyi syksyllå ja talvella lokakuun 59.1±1.5%:sta 72.5±2.0%:i huhtikuussa. Kåyttåmållå Pacen ja Rathbunin (1945) ruumiin kokonaisrasvapitoisuude laskukaavaa (rasva % = 100 - vesi %/0.732) huomattiin tamån vesimåårån lisaåntymis johtuvan samanaikaisesta rasvapitoisuuden våhenemisesta. Rasvapitoisuus laski lokakuun maksimiarvosta 18.9±2.6% ruumiinpainosta huhtikuun minimiarvoon, joka oli 0.9±2.7% ruumiinpainosta. Kesållå rasvapitoisuus lisåantyi puolestaan vesipitoisuuden kustannuksella. Talvella jåkålåravinnolla (joulu-huhtikuussa) veden kaytto vaihteli vålilla 30.8±5.2 ja 43.6±13.5 ml vrk-1kg-1 mutta se kohosi melkein nelinkertaisesti kesalla (keså-elokuussa) maksimiarvoonsa 117.7+5.9 ml vrk-1 kg-1 elokuussa. Veden kåyton ja ravinnon oton seka veden kåyton jaympåriston lampotilan vålilla oli positiivinen korrelaatio. Viimeksi mainittu korrelaatio voi johtua våliaikaisesta riippuvuudesta ravinnonoton ja ympåriston låmpotilan vålillå.